Homologous recombination repair deficient prostate cancer represents an immunologically distinct subtype. (31st December 2022) - van Wilpe, Sandra; Simnica, Donjetë; Slootbeek, Peter; van Ee, Thomas; Pamidimarri Naga, Samhita; Gorris, Mark A. J.; van der Woude, Lieke L.; Sultan, Shabaz; Koornstra, Rutger H. T.; van Oort, Inge M.; Gerritsen, Winald R.; Kroeze, Leonie I.; et al.
ABSTRACT: Homologous recombination repair deficiency (HRD) is observed in 10% of patients with castrate-resistant prostate cancer (PCa). Preliminary data suggest that HRD-PCa might be more responsive to immune checkpoint inhibitors (ICIs). In this study, we compare the tumor immune landscape and peripheral T cell receptor (TCR) repertoire of patients with and without HRD-PCa to gain further insight into the immunogenicity of HRD-PCa. Immunohistochemistry was performed on tumor tissue of 81 patients, including 15 patients with HRD-PCa. Peripheral TCR sequencing was performed in a partially overlapping cohort of 48 patients, including 16 patients with HRD-PCa. HRD patients more frequently had intratumoral CD3 +, CD3 + CD8 − FoxP3 − or Foxp3 + TILs above median compared to patients without DNA damage repair alterations (DDRwt; CD3 + and Foxp3 + : 77% vs 35%, p = .013; CD3 + CD8 − FoxP3 − : 80% vs 44%, p = .031). No significant difference in CD8 + TILs or PD-L1 expression was observed. In peripheral blood, HRD patients displayed a more diverse TCR repertoire compared to DDRwt patients (p = .014). Additionally, HRD patients shared TCR clusters with low generation probability, suggesting patient-overlapping T cell responses. A pooled analysis of clinical data from 227 patients with molecularly characterized PCa suggested increased efficacy of ICIs in HRD-PCa. In conclusion, patients with HRD-PCa display increased TIL density and an altered peripheral TCR repertoire. Further research into the efficacy of ICIs and the presence of shared neoantigens in HRD-PCa is warranted.